2021
DOI: 10.21203/rs.3.rs-418435/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and Bacteriological features of spontaneous bacterial peritonitis in Malagasy patients with Cirrhosis

Abstract: Background: Spontaneous bacterial peritonitis (SBP) represent frequent and serious complications in cirrhosis patients with ascites. Our aim was to describe the clinical and bacteriological characteristics of SBP in Madagascar.Methods: This is a 21-month prospective study between January 2018 and October 2019, including hospitalized patients with cirrhosis, with clinical and biological symptoms of SBP.Results: Thirty-three patients were included. The mean age was 48.09 ± 13.55 years (extremes: 19 – 78 years),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(26 reference statements)
0
0
1
Order By: Relevance
“…Previous studies have shown that the clinical manifestations of SBP are non-speci c. The most common symptoms of SBP are fever, abdominal pain, hepatic encephalopathy, abdominal tenderness, diarrhea, intestinal obstruction, shock, and hypothermia. Some studies reported that abdominal pain, fever, and diarrhea were the most common presenting symptoms of SBP [25]. Our ndings showed signi cant differences between the SBP and non-SBP groups in terms of abdominal pain, diarrhea, nausea, abdominal tenderness, rebound tenderness, abdominal muscle rigidity, and confusion, but no signi cant differences between temperature and abdominal distension.…”
Section: Clinical Usecontrasting
confidence: 42%
“…Previous studies have shown that the clinical manifestations of SBP are non-speci c. The most common symptoms of SBP are fever, abdominal pain, hepatic encephalopathy, abdominal tenderness, diarrhea, intestinal obstruction, shock, and hypothermia. Some studies reported that abdominal pain, fever, and diarrhea were the most common presenting symptoms of SBP [25]. Our ndings showed signi cant differences between the SBP and non-SBP groups in terms of abdominal pain, diarrhea, nausea, abdominal tenderness, rebound tenderness, abdominal muscle rigidity, and confusion, but no signi cant differences between temperature and abdominal distension.…”
Section: Clinical Usecontrasting
confidence: 42%